Selectivity and efficacy of PROTOX inhibitors in cassava varieties cultivated in clayey and sandy soils (Acta Scientiarum. Agronomy, 2022)
The selectivity and efficacy of protoporphyrinogen oxidase (PROTOX) inhibitor herbicides in cassava varieties depend on product formulation, dosage, and soil texture. The aim of this study was to assess the selectivity and efficacy of flumioxazin and sulfentrazone in the cassava variety ‘IPR B36’ and the clone ‘VN 117’. Two experiments were carried out: one in a clayey soil and one in a sandy soil. Both experiments were laid in a split-plot randomized block design with three replicates. The two cassava varieties were used as main plots, with subplots consisting in 10 treatments including, flumioxazin at 50, 75, 100, and 125 g ha-1; sulfentrazone at 250, 500, 750, and 1000 g ha-1; one weed-free control, and one unweeded control. Flumioxazin (â‰¥75 g ha-1) and sulfentrazone (â‰¥250 g ha-1) achieved mean weed control rates > 70 and 90% in both types of soil for up to 90 days after application. Flumioxazin exhibited fewer residual effects on the cassava varieties than sulfentrazone, particularly in clayey soil. Flumioxazin was selective to the different cassava varieties planted in both soil types, whereas sulfentrazone was more selective in clayey soil. PROTOX inhibitors were effective in controlling weed growth in cassava plots, and there were no varietal differences in herbicide selectivity; however, the use of sulfentrazone should be restricted to maximum spray rates of 250 g ha-1 in sandy soils.